Touristic activity in Suceava County - Elisabeta Rosu (Agrarian Economy and Rural Development - Realities and Perspectives for Romania. 7th Edition of the International Symposium, November 2016, Bucharest, 2016)
The natural and anthropic tourism potential of the Suceava county characterized by numerous natural reserves, many of them unique in the world, by the variety, density and value of historic, religious and architecture monuments are creating conditions for the county Suceava to be a tourism destination chosen, both for the Romanian and foreign tourists. This approach is intended to be an analysis of the main indicators of tourism activity in Suceava county during 2001-2014.
Keywords: L8; L83; Q2; 330; tourism potential; tourism activity indicators; Suceava county